Recent developments in the enhancement of some postharvest biocontrol agents with unconventional chemicals compounds. (August 2018) - Zhang, Hongyin; Mahunu, Gustav Komla; Castoria, Raffaello; Yang, Qiya; Apaliya, Maurice Tibiru
Abstract: Background: Produce are susceptible to microbial attack from diverse sources and the use of novel BCAs has gained recognition as alternative and sustainable applications to lessen the current emerging problems with synthetic fungicide use. Most researchers recommend the combination of two or more biocontrol agents in postharvest diseases control. To this end, the enhancement of biocontrol agents and the mechanisms of action in biocontrol systems have attracted many research interests. In this regard, there have been remarkable efforts to develop a multifaceted system approach for disease control. Scope and approach: It has been recognized that the various methods of biological control act together additively or synergistically to achieve significant commercial level of 97–99% disease control. The integration of microbial agents with a wide range of unconventional chemicals and their corresponding mechanisms of action to controlling postharvest fungal pathogens of fruits has been proven be successful. Key findings and conclusions: In this review, the combined strategy of unconventional chemical compounds and other BCAs have contributed to varied degree of postharvest diseases control. The beneficial effects of these methods depend on the appropriate combination of the agents based on adequate knowledge of their mechanisms of action in the biocontrol system. Lastly, efforts to upscale these methods to commercial implementation level must be given the necessary consideration. Highlights: Unconventional chemical compounds can form biofilms protection of yeasts in the biocontrol system. Biocompatibility effects of combined treatment reduce natural decay and increase the fruit defense responses to pathogen. The two treatments together produce additive or synergistic, which surpass their individual effect.